The Role of Governance, Accounting Information Systems, and Internal Controls in Cooperative Financial Performance - I Kadek Yasa Saputra; Sunitha Devi; Nyoman Ayu Wulan Trisna Dewi (English Education Department STKIP Agama Hindu Singaraja, 2026)
Cooperatives play a strategic role in promoting economic development, community empowerment, and organizational learning. However, many cooperatives continue to face challenges in maintaining sustainable financial performance. This study aimed to examine the effects of Good Corporate Governance (GCG), Accounting Information Systems (AIS), and Internal Control Systems (ICS) on the financial performance of cooperatives in Karangasem Regency, Bali. A quantitative approach with an associative research design was employed. The population consisted of 231 active cooperatives, from which 15 cooperatives were selected using purposive sampling. The study involved 60 respondents, including chairpersons, treasurers, accounting staff, and cashiers. Data were collected through questionnaires and analyzed using multiple linear regression with SPSS 25. The findings revealed that Good Corporate Governance positively and significantly affected financial performance (β = .418, p < .001), making it the strongest predictor among the variables examined. Accounting Information Systems also showed a positive and significant effect (β = .252, p = .020), while Internal Control Systems positively and significantly influenced financial performance (β = .303, p = .002). Furthermore, the regression model explained 74.9% of the variance in financial performance (Adjusted R² = .749). These findings suggest that strengthening governance practices, improving accounting information systems, and enhancing internal control mechanisms are essential for improving cooperative financial performance. The study contributes to the literature by highlighting the importance of governance, information management, and organizational control in supporting cooperative sustainability, financial literacy, and organizational learning